SUICIDAL THOUGHTS AND BEHAVIORS AMONG COLLEGE STUDENTS - Santillán Torres Torija, Carolina; Suárez Ortiz, Josué Omar; Ortiz Texis, Zyanya; Corchado Vargas, Angel (Revista Electrónica de Psicología Iztacala, 2024)
Death by suicide among young people continues to be an important mental health concern because of its high prevalence specially in the period between ages 15 and 29. Suicidal thoughts and behaviors seen as a continuum involve suicidal ideation (SI), suicidal plan (SP) and suicidal attempt (SA). Several studies have shown that suicide related behaviors are correlated with hopelessness, have a higher prevalence in women and are negatively related to academic performance. Accordingly, the purpose of this research was to describe rates of suicidal thoughts and behaviors (SI, SP and SA and hopelessness) among a sample of 10,307 Mexican entering freshmen at a health and biological sciences campus. Results showed that: a) women had higher prevalences of SI, SA and SP, b) academic achievement was negatively correlated with suicidal behaviors, and c) hopelessness was positively correlated with suicidal behaviors. Actions need to be taken in order to prevent, and refer students at risk opportunely.